Analysis of lncRNAs expression in monocytes and osteoclasts of rheumatoid arthritis patients - Amaral, Inês Filipa Pereira Abrunhosa (2019)
Rheumatoid arthritis (RA) is a chronic inflammatory immune-mediated rheumatic disease. Bone erosion is one of the hallmarks of RA pathophysiology and is associated with disease severity. Bone erosions in RA patients result from an imbalanced bone metabolism due, in part, to excessive osteoclastogenesis (the process by which precursor cells of the monocyte lineage differentiate into osteoclasts) and osteoclastic activity. Variable expression of long non-coding RNAs (lncRNAs) has been observed during mouse osteoclastogenesis, suggesting a physiologic role for lncRNAs in the process. In RA patients, lncRNA expression has been further shown to be altered in cellular types critical for its pathophysiology, like peripheral blood mononuclear leukocytes and activated fibroblast-like synoviocytes, in comparison to healthy controls. However, no study has yet examined lncRNA expression in monocytes and osteoclasts of RA patients. This work aims to address this question by analyzing the expression of a panel of 8 lncRNAs (GAS5, NEAT1, Meg3, DANCR, HOTAIR, Meg9, H19, and Sox2OT) in monocytes and osteoclasts of early arthritis patients, established RA patients and healthy controls. Both groups of patients were recruited at the Rheumatology Department, Hospital de Santa Maria, Lisbon Academic Medical Centre, Portugal. Age and sex matched donors were used as healthy controls. Heparinized blood was collected from each participant. Peripheral blood mononuclear cells (PBMCs) were isolated from whole blood samples by density gradient centrifugation. Adherent monocytes were in vitro differentiated into osteoclasts by a 21-day differentiation protocol. Total RNA was extracted from both monocytes and osteoclasts, for further analysis of lncRNA expression by real-time quantitative PCR (RT-qPCR). LncRNA expression analysis was performed for seventeen subjects, including 7 established rheumatoid arthritis patients, 3 early arthritis patients and 7 healthy donors. In vitro osteoclastogenesis produced a substantially higher number of osteoclasts in early arthritis patients, when compared to healthy controls. From our lncRNA panel, only GAS5, NEAT1, and DANCR presented a measurable expression in all tested samples. Our results showed an increased expression of NEAT1 and GAS5 along with a decreased expression of DANCR in monocytes of established RA patients, in comparison to those of healthy controls. An increased expression of NEAT1 along with a decreased expression of GAS5 and DANCR was observed in osteoclasts of early arthritis patients, when compared to those of healthy controls. No statistically significant differences were found for both analyses. Our data are consistent with an increased osteoclastogenic potential of peripheral monocytes of early arthritis patients, and thus, with an imbalanced bone metabolism in this pathological condition. Overall, our results prompted us to suggest that the lncRNAs here analyzed may in fact play a role in osteoclastogenesis in RA, as an altered lncRNA expression was observed in monocytes of early arthritis and established RA patients, when compared to healthy controls.